Evaluation of Hypochlorite Effectiveness as a Disinfectant Against Aerobic Bacteria - Dian Yudianto; Anjas Wilapangga; Errol Rakhmad Noordam; Bangun Sutyono; Trisna Permadi (HM Publisher, 2025)
Hypochlorite compounds, including calcium hypochlorite (Ca(OCl)₂) and sodium hypochlorite (NaOCl), are widely recognized for their broad-spectrum antimicrobial properties. This study aimed to evaluate the effectiveness of hypochlorite as a disinfectant against aerobic bacteria, providing insights into its application in infection control and water treatment. The study employed the aerobic bacteria number test, also known as the total plate count method, to enumerate bacterial colonies before and after exposure to varying concentrations of hypochlorite solution. Water samples were collected from different sources, including an emergency room floor, a pharmaceutical installation, and a hospital inpatient room. Serial dilutions of the water samples were prepared and plated on nutrient agar, followed by incubation and colony counting to determine the bacterial load. The percentage reduction in bacterial numbers was calculated for each hypochlorite dose. The results demonstrated a significant reduction in bacterial populations following hypochlorite treatment. A dose of 30 mL/5 L (6 μL/mL) reduced the average number of bacteria by 83.29%, A dose of 60 mL/5 L (12 μL/mL) reduced the average number of bacteria by 98.60%, A dose of 120 mL/5 L (24 μL/mL) reduced the average number of bacteria by 99.84%, A dose of 240 mL/5L (48 μL/mL) reduced the average number of bacteria by 99.98%, A dose of 480 mL/5L (96 μL/mL) reduced the average number of bacteria by 100%. The extent of bacterial reduction was directly proportional to the hypochlorite dose, indicating a clear dose-response relationship. In conclusion, this study confirms the efficacy of hypochlorite as a disinfectant against aerobic bacteria. A hypochlorite dose of 480mL/5L (96 μL/mL) effectively achieved complete bacterial elimination under the tested conditions. The results support its use in various applications, including disinfection of surfaces and water purification.